Daño renal agudo como factor predictor de mortalidad intrahospitalaria en cirrosis hepática descompensada en el Hospital Belén de Trujillo - Rodríguez Palomino, Carla Patricia (2015)
Determine whether the acute kidney injury is predictor of hospital mortality in decompensated liver cirrhosis in the Bethlehem Hospital of Trujillo. Methods: A study of, analytical, observational, retrospective cohort was conducted. The study population consisted of 84 patients with decompensated cirrhosis according to inclusion and exclusion criteria established divided into two groups: with and without acute kidney injury. Results: The mortality rate in patients with and without acute renal injury was 41 % and 20 % respectively. The relative risk of acute kidney injury in relation to hospital mortality was 2.12 (p < 0.05). Conclusions: Acute kidney injury is a risk factor for mortality in patients with penetrating abdominal trauma in the Bethlehem Hospital of Trujillo